Technology and Developing Countries: practical applications theoretical issues - Richard Heeks;Prabhakara (ed.) (London, 1995)
This volume contains the proceedings of the international conference on 'Science and Technology in Third World Development' held at the University of Strathclyde, Glasgow, Scotland in April 1993, and organised by the Science, Technology and Development Forum in association with the UK Development Studies Association; the Developing Countries Research Unit, University of Strathclyde; and the British Council. What follows in this introduction is a summary of some of the findings and issues presented at the conference.
Keywords: Economic-technological aspects